Land use conflicts in central Sudan: Perception and local coping mechanisms. (January 2015) - Adam, Yahia Omar; Pretzsch, Jürgen; Darr, Dietrich
Highlights: The respondents' perception of the conflict was ascertained and classified. Perception and coping mechanism scores were computed. Correlations between actors' characteristics and certain coping mechanisms were made. Local coping mechanisms for managing the land use conflicts were recognized. Abstract: Farmer-herder conflicts for the use of land represent a significant challenge for rural communities and the local authorities in Sudan. The study objectives were to (i) recognize farmers' and herders' perception on the conflict situation; (ii) elucidate and analyze the relationship between conflict perception and the actors' socioeconomic characteristics; and (iii) recognize the local coping mechanisms for managing these land use conflicts. The data were collected from 150 farmers and 50 herders randomly selected and interviewed in Sinnar State, Sudan in November–December, 2011. Quantitative data were analyzed using descriptive statistics, multiple regression and Pearson correlation, while context analysis was used to analyze the qualitative data. The study results revealed three perceptions of conflict among farmers and herders. There was significant correlation between some actors' socioeconomic characteristics and their perception of land use conflict as a 'threat' and as a 'loss'. The study identified fourteen coping strategies for managing land use conflicts between farmers and herders locally. The study concluded that farmer–herder conflicts in central Sudan are manageable since the actors' perceptions of the conflict are not particularly disparate.